Climate Transition Risks and the Energy Sector - Viral V. Acharya; Stefano Giglio; Stefano Pastore; Johannes Stroebel; Zhenhao Tan; Tiffany Yong (CESifo GmbH, 2025)
We build a general equilibrium model to study how climate transition risks affect energy prices and the valuations of different firms in the energy sector. We consider two types of fossil fuel firms: incumbents that have developed oil reserves they can extract today or tomorrow, and new entrants that must invest in exploration and drilling today to have reserves to potentially extract tomorrow. There are also renewable energy firms that produce emission-free energy but cannot currently serve non-electrifiable sectors of the economy. We analyze three sources of climate transition risk: (i) changes in the probability of a technological breakthrough that allows renewable energy firms to serve all economic sectors; (ii) changes in expected future taxes on carbon emissions; and (iii) restrictions on today's development of additional fossil fuel production capacity. We show that the different transition risk—and, importantly, uncertainty about their realizations—have distinct effects on firms' decisions, on their valuations, and on equilibrium energy prices. We provide empirical support for the heterogeneous effects of different transition risks on energy prices and stock returns of firms in different energy sub-sectors.
Keywords: E31; Q35; Q38; Q43; Q54; Q58; 330; climate change; renewable energy; green transition; policy uncertainty; fossil fuel firms; brown firms; carbon tax; drilling restrictions; oil prices